Carbon Capture Enhancement by Water-Based Nanofluids in a Hollow Fiber Membrane Contactor - Yuan, Cuiting; Pan, Zhen; Wang, Yan; Baena-Moreno, Francisco M.; Constantinou, Achilleas; Zhang, Zhien (My University, 2023)
Nanoparticles are being used in the CO2 solvents to improve the capture performance. Herein, a 2D model is proposed to study the CO2 capture performance from a gaseous mixture using a hollow fiber membrane contactor (HFMC). Both water-based nanofluids of carbon nanotubes (CNT) and SiO2 are deployed as the carbon absorbents. It is verified that Brownian motion and grazing effect are the major reasons to enhance the mass transfer of nanofluids. The simulation findings show that the modeling data conform well with the experimental studies. The root-mean-square errors for SiO2 nanofluid and CNT nanofluid are 2.37% and 2.56%, respectively. When the amounts of nanoparticles increase between 0.02 and 0.06 wt%, CO2 capture efficiencies of SiO2 and CNT nanofluids increase by 7.92% and 13.17%, respectively. Also, the CNT nanofluid has a better capture performance than the SiO2 nanofluid. Furthermore, research is conducted into how membrane characteristics affect HFMC performance. It is indicated that increasing the membrane porosity and decreasing the membrane tortuosity have a positive impact on the capture efficiency. This work demonstrates the potentials in the use of nanoparticles in CO2 solvents and provides a solid theoretical basis for nanofluids to significantly enhance gas absorption.
Keywords: carbon capture; carbon nanotubes; membrane contactors; nanofluids; SiO2